Uma análise econométrica do impacto dos gastos públicos sobre a criminalidade no Brasil - Loureiro, André Oliveira Ferreira (2006)
Using a new panel dataset of the Brazilian States, it was estimated, by means of econometric models, the effect of social expenditure on enforcement and welfare on criminality during the period of 2001 to 2003. In contrast to past works developed in Brazil, which used basically data on murder, four kinds of offenses are analyzed: murder, robbery, larceny and kidnapping. Based on the economic theory of crime, we have evaluated the direction and the size of the effect of public spending, in addition to social factors, on the criminal behavior in the Brazilian States. Our results, using fixed effects and first differences to take unobserved effects into account, pointed out income inequality as an important factor to explain criminal behavior. Aiming to control simultaneity between spending on public safety and crime, it was still used instrumental variables, examining if there is a deterrence effect from law enforcement. It was observed that, even when the endogeneity issue is taken into account, there seems not to be a consistent deterrence effect of public spending on safety on crime in Brazil. In most estimates, public spending on welfare displayed a negative and robust effect on criminality, suggesting that this kind of expenditure is an important factor to reduce crime.